The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/17504589221094136
|View full text |Cite
|
Sign up to set email alerts
|

The role of the bedside assistant in robot-assisted surgery: A critical synthesis

Abstract: Introduction: Robot-assisted surgery has grown exponentially since its inception and first approval in the United States in the year 2000. The surgeon operating with the assistance of the robot sits remotely to the patient and another practitioner assists at the bedside. The role of the bedside assistant and the training that is required to undertake this role are understudied topics. Aim: To explore the functions, training and professional development of the bedside assistant in robot-assisted surgery and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 93 publications
(98 reference statements)
1
2
0
Order By: Relevance
“…Ultimately, it is also worth noting that BA in robotic-assisted laparoscopy could be proficient after 10–36 cases [ 33 , 34 ], which is consistent with the number required in our research. We suppose that a BA in robotic-assisted laparoscopy has a short learning curve, even for an inexperienced BA who also could be proficient rapidly.…”
Section: Discussionsupporting
confidence: 87%
“…Ultimately, it is also worth noting that BA in robotic-assisted laparoscopy could be proficient after 10–36 cases [ 33 , 34 ], which is consistent with the number required in our research. We suppose that a BA in robotic-assisted laparoscopy has a short learning curve, even for an inexperienced BA who also could be proficient rapidly.…”
Section: Discussionsupporting
confidence: 87%
“…In some cases, the role of the assistant is minimal and limited to bedside instrument exchange, camera cleaning, and port site closure. In other operations, the assistant must provide adept laparoscopic assistance and understand the flow and sequence of the operation at an advanced level [ 2 ]. The assistant’s experience—whether limited as a junior resident or extensive as a fellow—has been posited as important to the success of robotic surgery [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bedside assistance is frequently described as a stepping stone on the path to console surgeon [4][5][6]. Prior work has acknowledged the multiple skills required as an assistant, and learning curve analysis has suggested that 10-36 cases are required for proficient bedside assistance [2,7]. However, the actual training of assistants varies [3,6].…”
Section: Introductionmentioning
confidence: 99%